Menelisik MENELISIK KEBUDAYAAN BANTEN MELALUI PEMANFAATAN MEDIA VIRTUAL - Herdin Muhtarom (Jurnal Budaya Nusantara, 2021)
ABSTACT Indonesia has a variety of cultures that are formed from the diversity of ethnicities, languages, and races so that they have a value, characteristics and characteristics that are in accordance with the cultural origins of their respective regions or are often known as regional cultures. This study uses a type of literature study research in the process of obtaining information related to the research title. The purpose of this research is to find out about the process of investigating Banten culture through the use of virtual media in the digitalization era as a medium to preserve the philosophical values ​​contained in the culture in the Banten area. Virtual media in the era of digitalization is very easy to access so that it can provide an understanding process related to a culture by using information and communication technology. Keyword: Indonesia, Culture, Virtual Media